O discurso político da luta contra a pobreza : uma análise de sua produção e circulação no contexto brasileiro contemporâneo - Turati, Carlos Alberto (Universidade Federal de São Carlos, 2016)
In our research, we investigate the discourse on the fight against poverty in the contemporary Brazilian political sphere, by analyzing the aspects of constitution, formulation and circulation of this discourse. More specifically, we take as a starting point, for the analysis, a set of speeches presented by President Dilma Rousseff in 2011, the year in which the federal government has adopted the slogan Rich country is country without poverty, and has made the fight against poverty a central goal of government actions. Supported by theoretical and methodological framework of Discourse Analysis and having as main reference the work of Michel Pêcheux, we take as a theoretical presupposition that all discursive practice is entered in contradictory-unequal- overdetermined complex of discursive formations that characterizes the ideological instance in given historical conditions. Therefore, we consider the category of the material contradiction as a constitutive condition of the discursive process, such that we consider it as a theoretical principle that guides the research and, at the same time, as the object of analysis. From this perspective, first we search to understand some historical determinations of the processes of meaning production. Thus, we identified in the context of European industrialization that the hegemonic form of the fight against poverty, already in its origin, is constituted by a set of contradictions that indicate that its goal is first of all a goal of the ruling classes, having in the classical liberal thought the basis of its formation. Similarly, we have identified that in the historical context of the Brazilian national problems, since the extractive activities until the contemporary capitalism, certain meanings that relate poverty to the public menace and violence, that take it as an indirect social and economic concern and that constitute the poor as naturally incapable feature an elitist and vertical view of the problem. Then we investigated how the contemporary form of the discourse on the fight against poverty acquired a central role in Brazilian politics, becoming a kind of categorical imperative of political and discursive actions. We seek to identify how this discourse has its hegemonic reproduction guaranteed, where apparent and naturalized differences serve to cover the constitutive contradictions that materialize the class conflicts that generate social inequalities. Thus, we see how the forms of functioning of the discourse on the fight against poverty configure strategies by which its constitutive contradictions are rarefied, erased, displaced and forgotten. If the first and most apparent contradiction of this discourse is the fact that it becomes hegemonic under the dictates and the impulse of monetary institutions, in our analysis, we observed that its hegemonic condition in the Brazilian political field has its efficiency guaranteed because such discourse functions contradictorily as evidence, consensus and truth to be taught; it mutes the agents and processes of exploitation by the capital, producing consensus within the contradictions and operating a management of the polemic within the political field; it is based on moral, subjectifying the poverty; it produces an erosion of collective identities of resistance; it delegitimizes politically the organized groups and individuals in their fight against inequalities; and subjective the poor as economic subject in a passive dimension.
Keywords: Discurso da luta contra a pobreza; Discurso político; Análise do discurso; Contradição ideológica; Produção de consenso; Discourse of the fight against poverty; Political discourse; Discourse analysis; Ideological contradiction; Production of consensus; Moral effect in the discursive process; LINGUISTICA, LETRAS E ARTES::LINGUISTICA